2010
DOI: 10.2478/v10078-010-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Different Types of Observational Training on Motor Learning of Gymnastic Handstand

Abstract: The present study aimed at assessing the influence of three types of observational training on motor learning of gymnastic handstand. Fifty healthy male subjects (age 20.35±1.44)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
2
14
0
2
Order By: Relevance
“…It has to be noticed that simultaneous verbal instructions, which direct the attention of athletes to six key points of the skills, are crucial (Kernodle, Johnson, & Arnold, 2001). Maleki, Shafie, Nia, Zarghami, and Neisi (2010) demonstrated that feedback with model observation and simultaneous provision of verbal instructions improved learning of the skill of handstand, while feedback without verbal instructions did not showed results in skill learning.…”
Section: Introductionmentioning
confidence: 95%
“…It has to be noticed that simultaneous verbal instructions, which direct the attention of athletes to six key points of the skills, are crucial (Kernodle, Johnson, & Arnold, 2001). Maleki, Shafie, Nia, Zarghami, and Neisi (2010) demonstrated that feedback with model observation and simultaneous provision of verbal instructions improved learning of the skill of handstand, while feedback without verbal instructions did not showed results in skill learning.…”
Section: Introductionmentioning
confidence: 95%
“…Simultaneous verbal instructions, which accompanied the model demonstrations and direct the attention of the athletes in key points of the skills, are crucial (Derri et al, 2014). The results of the study conducted by Maleki, Shafie, Nia, Zarghami, and Neisi, (2010) have shown that feedback with model observation and simultaneous provision of verbal instructions improved learning in the skill of handstand, while feedback without verbal instructions did not show results in skills learning. Recently, Lazarides and Gorozides (2012) defined that the simultaneous use of video with verbal feedback is superior in comparison to the traditional method in teaching serving in volleyball to children of the first grade of high school and Lola, Tzetzis and Zetou (2012), defined that the video observation model effected on implicit practice in the development of decision making in volleyball serving.…”
Section: Jpes ®mentioning
confidence: 99%
“…video, live or virtual model), the viewing perspective, and the characteristics of the task, observer and model [ 19 ]. Studies that have examined modality have yielded no differences between live and video models for learning a springboard diving task [ 20 ], between live and animated models performing a handstand [ 21 , 22 ], or between live and virtual models demonstrating fly-fishing technique [ 23 ]. When viewing the action from a first-person perspective faster skill acquisition may occur, as this perspective requires fewer cognitive resources than does viewing the action from a third-person perspective (i.e.…”
Section: Introductionmentioning
confidence: 99%